Bouquillion, P., Ithurbide, C., & Mattelart , T. (Ed). (2024) Digital Platforms and The Global South. Reconfiguring power relations in the cultural industries - Luis Grillo, Marylin (2025)
The book Digital Platforms and The Global South. Reconfiguring Power Relations in the Cultural Industries, edited by Philippe Bouquillion, Christine Ithurbide, and Tristan Mattelart, analyzes how digital platforms are reshaping power relations in the cultural industries of the Global South. Through 13 chapters, the text highlights the importance of considering the historical, sociopolitical, and cultural specificities of countries in Asia, Africa, and Latin America, in contrast to the models imposed by the Global North. This book serves as a valuable tool for understanding the dynamics between platforms and users in the Global South, opening up spaces for critical analysis of power asymmetries in the digital age.